Impact of Gender on Pre-Purchasing Behaviour of Consumers of Electric Vehicle - Manandhar, Raju Bhai (Nepal Journal of Multidisciplinary Research, 2021)
The demand of electric vehicle is increasing day by day because of its contribution in environmental health. The main objective of this study was to explore the gender impact on pre-purchasing behaviour of consumers of electric vehicle. The study was based on the quantitative design. The study was conducted in the Kathmandu valley among the electric vehicle users. The total sample size was 55. The standard structured questionnaire survey was used to collect the data. the study found that majority (72.7%) of the owner of electric vehicle were male. comparatively higher number (23.6%) customers had given most important to the information of electric vehicle based own their previous experience whereas least (1.8%) customers had given most important to the information disseminated through advertisement. Similarly, higher numbers (61.8%) customers reported that if they had any doubts or queries about the electric vehicle before purchasing decision, they directly consulted with the Company dealer to be clear in their queries. There was no impact of gender on pre-purchasing behaviour of customers of electric vehicles. Both male and female had similar practice of seeking the information before taking purchase decision. The future researcher should conduct the research on the purchase decision factors related to the electric vehicle users.